2018
DOI: 10.1186/s12943-018-0868-z
|View full text |Cite
|
Sign up to set email alerts
|

Tip110/SART3 regulates IL-8 expression and predicts the clinical outcomes in melanoma

Abstract: Tip110, an important regulator of several oncogenic proteins, was significantly downregulated in human metastatic melanoma cells exposed to a hypoxic condition. Therefore, in this study, we set to determine whether differential expression of Tip110 could be an important indicator for melanoma tumorigenesis and metastasis. We found that in melanoma, but not in other cancer types, Tip110 knockdown enhanced significant expression and secretion of IL-8 and melanoma cells invasions. This induction was further poten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 13 publications
1
17
0
Order By: Relevance
“…Studies have shown that the expression of IL-8 in melanoma is regulated via NF-κB. When NF-κB is translocated to the nucleus, IL-8 expression increases, leading to the promotion of a more favorable microenvironment for metastasis [80,81]. Our results indicated that both IL-6 and IL-8 expression levels decreased upon diminution of PKC-ι [67].…”
Section: A Schematic Summary Of the Regulation Of The Expression Of Pmentioning
confidence: 54%
“…Studies have shown that the expression of IL-8 in melanoma is regulated via NF-κB. When NF-κB is translocated to the nucleus, IL-8 expression increases, leading to the promotion of a more favorable microenvironment for metastasis [80,81]. Our results indicated that both IL-6 and IL-8 expression levels decreased upon diminution of PKC-ι [67].…”
Section: A Schematic Summary Of the Regulation Of The Expression Of Pmentioning
confidence: 54%
“…Melanoma cells have been reported to express IL-8 and this influences their oncogenic properties [ 12 , 19 ]. IL-8 follows the evolution of melanoma, progression, and regression under treatment, reflecting the stage of the disease [ 20 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that the expression of IL-8 in melanoma is regulated via NF-κB. When NF-κB is translocated to the nucleus, IL-8 expression increases, leading to the promotion of a more favorable microenvironment for metastasis (53,54). The results of this study indicated that both IL-6 and IL-8 expression levels decrease upon transfection with PKC-ι siRNA.…”
Section: Discussionmentioning
confidence: 55%